x1 and x2 are solutions of x^2-x+1=0. What is the value of the sum (x1^2-x1)^1000 + (x2^2-x2)^1000 ?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

x1 and x2 are given as the solutions of x^2 - x + 1 = 0

So if we substitute x with x1 we get x1^2 - x1 + 1 = 0

=> x1^2 - x1 = -1

Similarly with x2, x2^2 - x2 + 1 = 0

=> x2^2 - x2 = -1

The required sum is (x1^2-x1)^1000 + (x2^2-x2)^1000

=> -1^1000 + -1^1000

=> 1 + 1

=> 2

The required sum is 2.

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial